Pembelajaran Mendalam: Transformasi Pembelajaran Menuju Pendidikan Bermutu - Daris (CV. Biha Cendekia, 2025)
This study describes the deep learning framework as a transformative approach to education aimed at achieving quality, inclusive, and equitable learning for all students. Using literature review with a theoretical synthesis approach, it examines and integrates relevant theories, including a 2025 academic paper on deep learning published by the Ministry of Primary and Secondary Education. The approach emphasizes not only conceptual understanding but also the development of lifelong learner dispositions through mindful, meaningful, and joyful learning. It integrates cognitive, emotional, sensory, and physical dimensions to encourage students to understand, apply, and reflect on knowledge. The framework comprises graduate profile dimensions, learning principles, defined learning experiences, and an instructional framework that specifies teaching strategies and support structures. Student-centered by design, this approach is bottom-up rather than top-down, and contextual rather than merely textual. Deep learning requires systemic change through optimizing educator competencies, leveraging digital technology, fostering inclusive learning environment, and strengthening learning partnerships. As such, it serves as a strategic pathway for creating an education system that is equitable, high quality, and relevant to contemporary needs.